Interaksi sosial antara Suku Dayak dan Suku Banjar di Kalimantan - Lena Selvia; Sunarso Sunarso (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
Indonesia has a geographically vast area which results various daily ways of life and living habits that shapes culture and custom diversity. Indonesia consists of thousands of developing customs and tribes. The diversity of local customs and cultures in society contributes to social interaction among one tribe to another. The purpose of this study is to describe the cultural diversity found in the Dayak and Banjar tribes of Borneo. Each tribe has a unique culture with its own distinct as an identity to keep its existence, such as the cultural diversity of Dayak and Banjar tribes in Borneo that can affect relationships between the two tribes. The article used literary methods by collecting relevant reference sources from books, journals, researches, and other resources. The results show that diversity can cause conflict, even though conflict have occurred, it does not mean that the Dayak and Banjar tribes are intolerant. Each tribe has a strong culture and mutual cooperation to protect unity. They live on the same island with mutual respect and they respect cultural diversity. The interaction between the Dayak and Banjar tribes that appreciate each other's customs and cultures preserve the culture itself. The customs and cultures that developed in the Dayak and Banjar tribes serve as a source of harmony, with an understanding that they came from the same ancestors, and the awareness that they have a brotherly relationship contributes to values of trust, tolerance, and mutual cooperation between the tribes.